Organoids in biliary research: insights into developmental signaling and applications in disease modeling - Peng, Boming; Huang, Min; Zhang, Jianquan; Xiang, Yang (Frontiers in Cell and Developmental Biology, 2025)
The embryonic development of the biliary system is orchestrated by complex signaling pathways, including Notch, TGF-β, Wnt, and GFs, which regulate biliary stem/progenitor cell fate, polarity, and ductal morphogenesis. These pathways not only govern physiological development but are also deeply implicated in pathological processes such as inflammation, fibrosis, and carcinogenesis. However, conventional two-dimensional culture systems and animal models fall short in replicating the spatial structure, developmental dynamics, and human-specific molecular context of the biliary tract. As a result, bile duct organoids derived from various cellular sources have emerged as powerful in vitro platforms, capable of reconstructing key features of biliary architecture and function. Organoids not only respond to, but also enable the controlled manipulation of, developmental signaling pathways. These systems have revealed the dual roles of Wnt, Notch, TGF-β, and GFs in both tissue homeostasis and disease progression. Recent studies have successfully applied biliary organoid models to explore the mechanisms underlying primary sclerosing cholangitis, biliary atresia, cholangiocarcinoma, and gallbladder cancer, identifying critical signaling axes and regulatory networks. This review systematically reviews the roles of key signaling pathways in bile duct development and their regulatory mechanisms in organoid construction, with a particular focus on the applications of organoid models in elucidating signaling pathway abnormalities, uncovering disease mechanisms, and identifying potential therapeutic targets. It further provides a perspective on their prospects and challenges in the development of precision therapeutic strategies and clinical translation.